PENERAPAN ERP PADA SISTEM INFORMASI MANAJEMEN PERUSAHAAN DI BIDANG KEUANGAN MENGGUNAKAN APLIKASI ZAHIR ACCOUNTING PADA TOKO ABC - Afriyanti Dwi Kartika; Mutiara Raudhatul Jannah; Intan Yuliana Putri; Arif Roska Perdana; Fauzan Maizardi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
UMKM are one of the economic actors whose support national development. However, some of them experience problems in accounting reporting so it’s difficult to assess business success. ABC Stores are trading sector UMKM in Padang City which still record and process financial data manually so they are prone to errors. Technological developments enable company’s business process optimalization. This research carried out implementation of Zahir Accounting ERP version 6.0 which has simple design, uses Indonesian, and automation of accounting so it’s easy for non-accounting users to understand. Implementation on Toko ABC is applied to process of buying, selling, recording and financial reporting. Research method begins with data collection through observation, interviews, and literature studies. Then data from Toko ABC is implemented in Zahir Accounting. Based on the implementation, Zahir Accounting can be a solution for UMKM in recording and reporting finances because integrated system between business processes and financial reports.